Anti-inflammatory potential of a malleable matrix composed of fermented whey proteins and lactic acid bacteria in an atopic dermatitis model - Dupont Claude; Beaulieu Josée; Lemieux Pierre (BMC, 2007)
Abstract Background Over the last 10 years, whey proteins have received considerable attention in the area of functional foods and nutraceuticals. In this paper, a novel fermented whey protein-based product described as a gel-like Malleable Protein Matrix (MPM) has been tested for its anti-inflammatory activity. Preliminary in vitro results have already indicated that MPM could exert such an anti-inflammatory activity. Methods The systemic anti-inflammatory activity of the MPM was explored using the oxazolone-induced atopic contact dermatitis mouse model (ACD). Parameters including ear thickness, side effects as well as neutrophil extravasation were monitored. Results In the ACD model, the MPM exhibited an anti-inflammatory effect comparable to that of hydrocortisone (positive control). Mice fed with MPM showed strong reduction of the ear inflammation while no side effects, as compared to hydrocortisone, were observed. The MPM seemed to reduce neutrophil extravasation in tissue as evidenced by blood polymorphonuclear cells and ear myeloperoxidase content. Conclusion The anti-inflammatory activity demonstrated in the ACD model suggests that the mechanism of action of the MPM is different than that of hydrocortisone and could become a relevant product for people suffering from dermatological manifestations associated with immune dysfunctions such as allergies, eczema, dermatitis, and autoimmune diseases.